SELF-CONSISTENT CHEMICAL MODEL OF PARTIALLY IONIZED PLASMAS - Davletov, A.E. (Recent Contributions to Physics, 2008)
Starting from the Bogolyubov hierarchy in the pair correlation approximation and the expression for the free energy, taking into account interparticle interactions in the system, the ionization equilibrium and pair correlation functions have been determined. The numerical results and analysis implemented have shown that the correlation phenomena in partially ionized plasmas lead not only to the charge shielding but to the short-range order formation as well. Direct comparison of the obtained results with the quantum-mechanical fugacity expansion demonstrates that the approach developed describes adequately the behavior of partially ionized plasmas for moderate densities and high temperatures.